Immunosuppressive Effects of Natural α,β-Unsaturated Carbonyl-Based Compounds, and Their Analogs and Derivatives, on Immune Cells: A Review - Arshad, Laiba; Jantan, Ibrahim; Bukhari, Syed Nasir Abbas; Haque, Md. Areeful (Frontiers in Pharmacology, 2017)
The immune system is complex and pervasive as it functions to prevent or limit infections in the human body. In a healthy organism, the immune system and the redox balance of immune cells maintain homeostasis within the body. The failure to maintain the balance may lead to impaired immune response and either over activity or abnormally low activity of the immune cells resulting in autoimmune or immune deficiency diseases. Compounds containing α,β-unsaturated carbonyl-based moieties are often reactive. The reactivity of these groups is responsible for their diverse pharmacological activities, and the most important and widely studied include the natural compounds curcumin, chalcone and zerumbone. Numerous studies have revealed the mainly immunosuppressive and anti-inflammatory activities of the aforesaid compounds. This review highlights the specific immunosuppressive effects of these natural α,β-unsaturated carbonyl-based compounds, and their analogues and derivatives on different types of immune cells of the innate (granulocytes, monocytes, macrophages and dendritic cells) and adaptive (T cells, B cells and natural killer cells) immune systems. The inhibitory effects of these compounds have been comprehensively studied on neutrophils, monocytes and macrophages but their effects on T cells, B cells, natural killer cells and dendritic cells have not been well investigated. It is of paramount importance to continue generating experimental data on the mechanisms of action of α,β-unsaturated carbonyl-based compounds on immune cells to provide useful information for ensuing research to discover new immunomodulating agents.